2017
DOI: 10.1177/1071100717740937
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Os Trigonum on CT Imaging

Abstract: Level III, retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 9 publications
0
53
0
7
Order By: Relevance
“…Because of this, he reasoned that after anterior dislocation, the Achilles pulled the talus posteriorly [17]. Conversely, other authors feel that in the unstable equinus position, an appropriately directed force could result in direct posterior extrusion [7,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this, he reasoned that after anterior dislocation, the Achilles pulled the talus posteriorly [17]. Conversely, other authors feel that in the unstable equinus position, an appropriately directed force could result in direct posterior extrusion [7,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Like pure ankle dislocations, bilateral os trigonum is uncommon. Zwiers et al found the incidence of bilateral os trigonums to be only 14.3% in their retrospective CT evaluation of 628 patients [20]. Injury of the os trigonum can occur by two different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Tanto o Os trigono quando o processo de Stieda são achados sem repercuções clínicas na população geral (15) . Conforme encontrado por Zwiers et al (16) , em estudo de avaliação tomográfica de 1256 tornozelos, que constatou uma prevalência de 30.3% de Os trigonum em pacientes assintomáticos, assim como a presença em 46.4% dos indivíduos que apresentavam quadro de impacto posterior, de maneira geral esse achado esteve presente em 23.7% dos tornozelos (16) . Na ausência de evidência de Os trigonum, o alargamento do tubérculo posterior do processo talar foi identificado em 34.9% dos tornozelos (16) .…”
Section: Discussionunclassified
“…Conforme encontrado por Zwiers et al (16) , em estudo de avaliação tomográfica de 1256 tornozelos, que constatou uma prevalência de 30.3% de Os trigonum em pacientes assintomáticos, assim como a presença em 46.4% dos indivíduos que apresentavam quadro de impacto posterior, de maneira geral esse achado esteve presente em 23.7% dos tornozelos (16) . Na ausência de evidência de Os trigonum, o alargamento do tubérculo posterior do processo talar foi identificado em 34.9% dos tornozelos (16) . Sugere-se que a sobrecarga repetida, e os microtraumas de repetição a qual a população que pratica atividade física e exige a flexão plantar forçada pode ser o fator desencadeante para sintomas da síndrome (3,7,9,15) .…”
Section: Discussionunclassified
“…Coskun et al (2009) evaluaron radiografías de 984 sujetos y establecieron que un 2,3 % de la población turca presenta OT. En cambio, Zwiers et al (2018) estudiaron 1256 tobillos y establecieron que un 32,5 % de la población presentó OT.…”
Section: Materials Y Métodounclassified